2014
DOI: 10.7314/apjcp.2014.15.7.3035
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lung Cancer in the Pakistani Population

Abstract: Background: Lung cancer is one of the most prevalent malignancies in the world and both incidence and mortality rates are continuing to rise in Pakistan. However, epidemiological studies to identify common lung cancer determinants in the Pakistani population have been limited. Materials and Methods: In this retrospective case-control study, 400 cases and 800 controls were enrolled from different hospitals of all provinces of Pakistan. Information about socio-demographic, occupational, lifestyle and dietary var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 37 publications
1
39
0
1
Order By: Relevance
“…In the Middle East countries, particularly in the middle and high-income countries, the incidence of cancer has increased substantially as behavioral risk factors such as smoking, unhealthy diet, physical inactivity and obesity in both adults and children have increased (Rahim et al, 2014;Kruk and Marchlewicz, 2013;Qin, 2013). The incidence of cancer can be reduced by primary prevention through adopting a healthy lifestyle and environmental interventions (Danaei, 2005;Luqman et al, 2014). However, studies conducted in developed and developing countries including Arabic and Middle East countries showed that public knowledge and awareness of cancer risk factors are poor (Breslow et al, 1997;Robb et al, 2009;Feizi et al, 2010;Ravichandran et al, 2010;Radi, 2013).…”
Section: Awareness Of Risk Factors For Cancer Among Omani Adults-a Comentioning
confidence: 99%
“…In the Middle East countries, particularly in the middle and high-income countries, the incidence of cancer has increased substantially as behavioral risk factors such as smoking, unhealthy diet, physical inactivity and obesity in both adults and children have increased (Rahim et al, 2014;Kruk and Marchlewicz, 2013;Qin, 2013). The incidence of cancer can be reduced by primary prevention through adopting a healthy lifestyle and environmental interventions (Danaei, 2005;Luqman et al, 2014). However, studies conducted in developed and developing countries including Arabic and Middle East countries showed that public knowledge and awareness of cancer risk factors are poor (Breslow et al, 1997;Robb et al, 2009;Feizi et al, 2010;Ravichandran et al, 2010;Radi, 2013).…”
Section: Awareness Of Risk Factors For Cancer Among Omani Adults-a Comentioning
confidence: 99%
“…Awareness of risks is the most commonly cited motivation to quit smoking, both by current and former smokers. It is also a better predictor for longterm abstinence before quitting (Hammond et al, 2004a;Hyland et al, 2004) and adopting healthy life styles has ever been associated with decreased development of chronic morbidities related to smoking (Tayyem et al, 2013;Luqman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More recent systematic review studies or case-control studies reported positive association between exposure to pesticides and several cancers including prostate cancer (Van Maele-Fabry and Willems, 2004;Koutros et al, 2010;Doolan G et al, 2014), non-Hodgkin lymphoma (NHL) (Merhi et al, 2007;Balasubramaniam et al, 2013;Yildirim et al, 2013;Schinasi and Leon, 2014), leukemia (Merhi et al, 2007;Van Maele-Fabry et al, 2008), multiple myeloma (Merhi et al, 2007) and lung cancer (Ganesh et al, 2011;Luqman et al, 2014). In the case of esophageal or gastric cancer, no relationship with pesticide usage was reported in recent Turkey study (Yildirim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%